A walk around the decarboxylative C-S cross-coupling reactions. (2nd January 2019) - Hosseinian, Akram; Nezhad, Parvaneh Delir Kheirollahi; Ahmadi, Sheida; Rahmani, Zahra; Monfared, Aazam
ABSTRACT: This review highlights a number of recent discoveries and advances in the construction of carbon-sulfur bonds through decarboxylative cross-coupling reactions between carboxylic acids and sulfur-containing coupling partners. Particular emphasis is placed on the mechanistic aspects of the reactions. GRAPHICAL ABSTRACT: